2016
DOI: 10.17795/ijpbs-2602
|View full text |Cite
|
Sign up to set email alerts
|

Locus of Control or Self-Esteem; Which One is the Best Predictor of Academic Achievement in Iranian College Students

Abstract: BackgroundSelf-esteem and behavioral consequences, which are due to external or internal locus of control, are effective on academic achievement of students.ObjectivesThe aim of this study was to determine the prediction of locus of control and self-esteem in academic achievement among the students.Materials and MethodsThis cross-sectional study was conducted on 300 college students in Kermanshah University of Medical Sciences in 2014. Data collection tools were in three sections: demographic, Rotter internal-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 18 publications
3
22
0
1
Order By: Relevance
“…The findings indicate a low level of regular physical activity in Iranian students, compared with students outside Iran (18,19). Several studies stated that college students in one of the most important groups should pay special attention to their health problems (20)(21)(22). The low statistics of regular physical activity in Iranian students and the lack of enough motivation for participation in such activities indicate the necessity of exploring the socio-cognitive determinants that impact on the creation of such behaviors in students.…”
Section: Discussionmentioning
confidence: 97%
“…The findings indicate a low level of regular physical activity in Iranian students, compared with students outside Iran (18,19). Several studies stated that college students in one of the most important groups should pay special attention to their health problems (20)(21)(22). The low statistics of regular physical activity in Iranian students and the lack of enough motivation for participation in such activities indicate the necessity of exploring the socio-cognitive determinants that impact on the creation of such behaviors in students.…”
Section: Discussionmentioning
confidence: 97%
“…Studies have shown that knowledge of the cognition of people at risk is essential for the development of preventive strategies [17,18]. Although identifying all the determinants affecting the performance of health behaviors is complicated, identifying some of them facilitates making predictions and helps health-promotion experts develop health-promoting interventions and programs [19]. The results of a systematic review study conducted by Holmes et al showed that using a theory or model can predict treatment adherence as a behavior only to a limited degree, and combining behavioral models and their constructs may provide a strengthened theoretical basis for the development and evaluation of interventions affecting treatment adherence [20].…”
Section: Introductionmentioning
confidence: 99%
“…Academic achievement is one of the most important academic learning and performance indicators for learners and has always attracted the attention of education science experts (1). Academic achievement is influenced by various factors such as knowledge structure and learning strategies (2). Learning strategies are methods learners' use that can guide their learning and thinking process; thus, the use of learning strategies can enhance learning (3,4).…”
Section: Introductionmentioning
confidence: 99%